Pakistan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper describes economic developments in Pakistan over the five-year period 1992/93-1996/97, with particular emphasis on the last two years. The paper discusses output and price developments, the performance of public sector enterprises, and the packages that were introduced by the new government to revive agriculture and industry. It discusses budgetary and fiscal policy developments, including a discussion of the important reform of the revenue-sharing arrangement between the federal government and the provinces. The paper also discusses developments in the monetary sector.